Granulocyte Colony Stimulating Factor (G-CSF) Quantitative Analysis In Plasmodium Vivax Infected Malaria Patients Experiencing Trombocytopenia - Gita Dwi Prasasty; R. A. Leni Septiana; Chairil Anwar; Dwi Handayani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Abstract Introduction : P. Vivax has been refered as pathological factor underlying increasing prevalences of haematological abnormality including anemia and thrombocytopenia. Through the day, exact mechanism of thrombocytopenia in malaria infection has yet come to a conclusion, several hypothesis are still in considered, phagocytosis and platelets aggregation remain the major disscussion topics. G-CSF, cytocine with elevated serum quantity in P. Vivax infections, were responsible in increasing phagoctytosis and conducting direct effect on platelets aggregation using adequate ADP. Increasing number of ADP in malaria cases were correlated with erythrocyte haemolitic, leading to increasing platelets aggregation. Although numerous hypothesis has been compelled, only a-few research publication has been made corresponding to G-CSF serum level on malaria P. Vivax infection and its correlations to thrombocytopenic events. Aim of study : To analyze the relations between G-CSF serum levels and parasite numbers towards platelets profile in infected malaria P. Vivax patients. Methods : Study design using Prospective analysis. Thirty six patients with single infection of Malaria Vivax in Puskesmas Sukamaju (Primary Heath Care Centre) and Puskesmas Kota Karang were assessed for G-CSF plasma levels, platelet counts, and MPV. Data analysis were conducted using Spearman correlation methods with SPSS. Results : Study results showing significant correlation between G-CSF serum levels towards Platelet conts (R = -0,397(p = 0,016)), without significant correlation between G-CSF and MPV value (p = 0,874) Conclusion : G-CSF serum levels were related with thrombocytopenia, with no correlation towards MPV. Keyword: G-CSF, P. vivax, Thrombocytopenia, MPV.